2013
DOI: 10.1002/jcb.24636
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐214 Protects Cardiac Myocytes Against H2O2‐Induced Injury

Abstract: Reactive oxygen species (ROS)-induced cardiac myocyte injury resulting from changes in the expression levels of multiple genes plays a critical role in the pathogenesis of numerous heart diseases. The purpose of this study was to determine the potential roles of microRNA-214 (miR-214) in hydrogen peroxide (H2O2)-mediated gene regulation in cardiac myocytes. In this study, we used quantitative real-time RT-PCR (qRT-PCR) to demonstrate that miR-214 was upregulated in cardiac myocytes after treatment with H2O2. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 48 publications
6
62
1
2
Order By: Relevance
“…This result suggests that miR-214 protects the heart by repressing cardiomyocyte apoptosis through inhibition of PTEN. Our previous study 19) has shown that PTEN is regulated by miR-214 and serves as an important target of miR-214 in cardiac myocytes. A similar study 20) showed that miR-214 protects the heart against I/R injury by blunting Ca 2+ overload and cell death in response to injury through its repression of NCX1, CaMKIIδ, CypD, and BIM.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that miR-214 protects the heart by repressing cardiomyocyte apoptosis through inhibition of PTEN. Our previous study 19) has shown that PTEN is regulated by miR-214 and serves as an important target of miR-214 in cardiac myocytes. A similar study 20) showed that miR-214 protects the heart against I/R injury by blunting Ca 2+ overload and cell death in response to injury through its repression of NCX1, CaMKIIδ, CypD, and BIM.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are implicated in the cellular response to oxidative stress via several different mechanisms [24][25][26][27] ; of these, the antioxidant defense system is responsible for preventing ROS accumulation during cerebral I/R. Some miRNAs directly target antioxidant/oxidant genes; for instance, miR-34a induces apoptosis in the human glioma cell line via enhanced nicotinamide adenine dinucleotide phosphate oxidase 2 expression and ROS production, 24 whereas miR-155 modulates ROS level by targeting SH2-domain-containing inositol 5-phosphatases in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…МикроРНК участвуют в клеточном ответе на окси-дантный стресс посредством различных механизмов [24][25][26][27]; одним из них является система антиоксидант-ной защиты, отвечающая за предотвращение накоп-ления АФК во время церебральной И/Р. Некоторые микроРНК нацелены непосредственно на антиокси-дантные/оксидантные гены; например микроРНК-34а индуцирует апоптоз в линии клеток глиомы чело-века путем повышения экспрессии никотинамид аде ниндинуклеотидфосфатоксидазы-2 и образования АФК [24], в то время как микроРНК-155 модулирует содержание АФК посредством влияния на SH2-домен-содержащую инозитол 5-фосфатазу в макрофагах [25].…”
Section: рисунок 4 микрорнк-424 стимулируют экспрессию и активность unclassified
See 1 more Smart Citation
“…A previous study also reported that miR-214 bound to the 3′-UTR of PTEN mRNA and facilitated the degradation of PTEN mRNA. 46) Thus, we investigated whether the decrease in the mRNA levels of HMG-CoAS, SQS, and PTEN was caused by an increase in miR-214 levels in the livers of SHRSP. No significant differences were observed in HMG-CoAS, SQS, or PTEN mRNA levels in the liver between SHRSP and WKY, although a slight decrease was noted in PTEN mRNA in SHRSP (Fig.…”
Section: Comparison Of Mpd and Mir-214 Expression Levels Between Shrsmentioning
confidence: 99%